2023
DOI: 10.1097/ccm.0000000000005894
|View full text |Cite
|
Sign up to set email alerts
|

Bringing the Promise of Artificial Intelligence to Critical Care: What the Experience With Sepsis Analytics Can Teach Us

Abstract: In 1985, development of a computer system called "Deep Thought" began at Carnegie Mellon University with the lofty objective of developing an autonomous system capable of outperforming the world's top chess grandmasters. Later renamed "Deep Blue, " this chess-playing expert system defeated world champion Gary Kasparov in 1997 in a six-game match. However, it was not until 2017 that a deep artificial neural network algorithm known as "AlphaZero" achieved super-human performance in several challenging games, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Despite major interest in strategies to relieve the morbidity and mortality of sepsis, novel therapeutics have failed to translate into meaningful patient-centered outcomes. The potential to improve care through the use of artificial intelligence is attractive, particularly with advances in machine learning in the past decade 22 , 23 . Unfortunately, the majority of algorithms designed to predict sepsis never make it to the bedside 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite major interest in strategies to relieve the morbidity and mortality of sepsis, novel therapeutics have failed to translate into meaningful patient-centered outcomes. The potential to improve care through the use of artificial intelligence is attractive, particularly with advances in machine learning in the past decade 22 , 23 . Unfortunately, the majority of algorithms designed to predict sepsis never make it to the bedside 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Future research is indicated on whether artificial intelligence deep learning models can be used to enhance prediction tools for both the purposes of patient selection and survival, as has begun in other areas of clinical practice. 16…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that combining the SAVE/RESP score with a comprehensive evaluation by an experienced multidisciplinary ECMO team would be best for decision making on determining ECMO candidacy and long-term prognosis until better prediction models are developed. Future research is indicated on whether artificial intelligence deep learning models can be used to enhance prediction tools for both the purposes of patient selection and survival, as has begun in other areas of clinical practice 16 …”
Section: Discussionmentioning
confidence: 99%
“…However, a recent systematic review of 494 AI studies using data obtained during an ICU stay found none that reported on patient outcomes following AI model integration [ 14 ]. Implementing AI tools has been described as an “afterthought” compared with investment in model development [ 16 ]. It could be speculated that these tools are not being studied and developed in a manner relevant to bedside clinicians, which could be a barrier to the clinical adoption of a particular tool.…”
Section: Discussionmentioning
confidence: 99%